2021
DOI: 10.3390/ijms22041712
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Receptors and Fibrinolysis

Abstract: The ability of cells to promote plasminogen activation on their surfaces is now well recognized, and several distinct cell surface proteins have been demonstrated to function as plasminogen receptors. Here, we review studies demonstrating that plasminogen bound to cells, in addition to plasminogen directly bound to fibrin, plays a major role in regulating fibrin surveillance. We focus on the ability of specific plasminogen receptors on eukaryotic cells to promote fibrinolysis in the in vivo setting by reviewin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 89 publications
0
16
0
Order By: Relevance
“…The plasminogen receptors function to stimulate tPA- and uPA-dependent plasminogen activation. In addition, they localize plasmin proteolytic activity to the cell surface and also protect both the plasminogen activators and plasmin from rapid inactivation by the abundant inhibitors that surround cells (reviewed in [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]). Plasminogen receptors are broadly distributed on both eukaryotic and prokaryotic cell types, and the majority of cells have a high capacity for binding plasminogen.…”
Section: Plasminogen Receptorsmentioning
confidence: 99%
“…The plasminogen receptors function to stimulate tPA- and uPA-dependent plasminogen activation. In addition, they localize plasmin proteolytic activity to the cell surface and also protect both the plasminogen activators and plasmin from rapid inactivation by the abundant inhibitors that surround cells (reviewed in [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]). Plasminogen receptors are broadly distributed on both eukaryotic and prokaryotic cell types, and the majority of cells have a high capacity for binding plasminogen.…”
Section: Plasminogen Receptorsmentioning
confidence: 99%
“…Plasmin generation proceeds at a slow rate but is accelerated by a group of cell surface proteins that bind plasminogen, called plasminogen receptors [55][56][57]. Plasminogen receptors localize the bound plasminogen near the vicinity of the tumor cell, allowing easy access by uPAR-bound uPA.…”
Section: Overview Of the Plasmin-plasminogen Activation Systemmentioning
confidence: 99%
“…Those that have a C-terminal lysine include αenolase [142], histone H2B [147,148], S100A4 [149], the annexin A2 heterotetramer (annexin A2 in complex with p11 also known as AIIt) [101], plasminogen (Plg)-RKT [150], TIP49a [151], and cytokeratin 8 [152]. Examples of plasminogen receptors that do not have the classic C-terminal lysine residue include high mobility group box-1 protein (HMGB-1) [56] (also known as amphoterin) and integrins, primarily those of the β2 inte-grin family [57] and glucose-regulated protein 78 [153]. It has been shown that a significant amount of the plasmin generating activity of malignant cancer cells is due to a novel, unidentified class of plasminogen receptors.…”
Section: Plasminogen Receptorsmentioning
confidence: 99%
“…It was shown that tPA could interact with Plg-R kt to promote PLG activation and local plasmin generation. This pathway could increase the proinflammatory effects induced by plasmin [82] . So, these different studies highlight diverse and sometimes opposite effects of tPA versus plasmin in activation of macrophages by LPS in vitro .…”
Section: Effects Of Tpa On Mononuclear Phagocyte Cellsmentioning
confidence: 99%